Bangladesh in the 1990s : selected studies - Schendel, Willem van.; Westergaard, Kirsten; European Network of Bangladesh Studies. Workshop (1994 : Zeist, Netherlands) (Dhaka, Bangladesh : Published for the European Network of Bangladesh Studies [by] University Press, 1997)
Selection of papers presented at the Workshop of the European Network of Bangladesh Studies at Zeist, Netherlands, in 1994.
BIED
Keywords: Bangladesh -- Scheduled tribes; Bangladesh -- Social conditions; Bangladesh -- Economic conditions